FAKTOR-FAKTOR YANG MEMPENGARUHI KETIDAKPATUHAN BEROBAT PADA PENDERITA TUBERKULOSIS DI PUSKESMAS KOTA BANDA ACEH - Cut Ana Martafari; Zuheri Zuheri (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2021)
Tuberculosis is a contagious disease caused by Mycobacterium tuberculosis. Indonesia is the country with the second highest prevalence of TB after India is getting annually that is 1 million new cases of TB. Pulmonary tuberculosis is a chronic disease with one of the keys to the success of its treatment is patient compliance. This infectious disease can actually be cured with effective treatment and management for at least 6 months. This study aims to determine the Factors that influence non-adherence of treatment of tuberculosis patients in primary health care center of Banda Aceh City. The type of this research is descriptive analytic by using cross sectional method. The sample was taken from 3 (three) work areas of primary health care center of Banda Aceh City with 33 samples and taken using purposive sampling technique. The results of the study found that there were 8 respondents who did not adhere to treatment. Most patients who are not adherent to treatment are 45 years old and are male. Factors affecting non-adherence to treatment were gender (0.038), drug side effects (0.024) and drug-taking control (0.000). While that did not affect non-compliance were age (0,539), education (0,626), knowledge level (0,691) and health service facilities (0,241). From all research results it is expected that health institutions should pay attention to and provide health services to be more accessible to the community and provide education prior to treatment and upon arrival of controls in TB patients.Keywords: Non adherence, Primary Health Care Facilities, Pulmonary TB